THE RELATIONSHIP BETWEEN THE SAMARKAND INSTITUTE OF ARCHITECTURE AND CIVIL ENGINEERING AND URBAN INFRASTRUCTURE DEVELOPMENT - Nasrullayevich, Sa’dullayev Ibrohim; o‘g‘li, Otaxanov Javlonbek Mammatsharip; o‘g‘li, Azizbek Shomurodov Rustam (Research Focus International Scientific Journal, 2026)
This article analyzes the relationship between the Samarkand Institute of Architecture and Civil Engineering and the development of urban infrastructure. The study examines the role of the institute in training specialists in engineering, architecture, and construction, as well as its scientific contributions to urban planning, transportation systems utilities, and housing development. It also highlights the interaction between higher education technological progress, and urbanization processes in Samarkand. The findings demonstrate that higher education institutions play a strategic role in shaping modern urban infrastructure.